Adiponectin levels in people with Latent Autoimmune Diabetes-a case control study - Jeffrey Stephens (BMC Research Notes, 2010)
To examine adiponectin levels in people with Latent Autoimmune Diabetes in Adults using a matched pair case control study. Patients with LADA (n = 64), were matched for sex with type 2 diabetic and non-diabetic controls. A matched paired T-test was used to examine average adiponectin levels in the LADA patients' versus controls. The average adiponectin level for the LADA patients was 9.96 μg/ml compared to 6.4 μg/ml for Type 2 matched controls and 9.6 μg/ml for non-diabetic controls. Mean difference for the LADA-type 2 comparison was calculated after data was log transformed and showed a difference of 1.58 μg/ml (95%CI: 1.28-1.95, p = 0.0001). There was no significant difference between LADA and non-diabetic controls (p = 0.54). Adiponectin levels are higher among people with LADA compared to those with type 2 diabetes and are equivalent to levels seen in non-diabetic controls. This suggests that risk of complications in LADA, as with type 1 diabetes may be related more to glycaemic control rather than to factors of the metabolic syndrome.